NGC 5846-UDG1: a galaxy formed mostly by star formation in massive, extremely dense clumps of gas - Danieli, Shany; Dokkum, Pieter van; Trujillo-Gomez, Sebastian; Kruijssen, Diederik; Romanowsky, Aaron J.; Carlsten, Scott; Shen, Zili; Li, Jiaxuan; Abraham, Roberto; Brodie, Jean; Conroy, Charlie; Gannon, Jonah S.; et al. (The astrophysical journal. Part 2, Letters, 2022)
It has been shown that ultra-diffuse galaxies (UDGs) have higher specific frequencies of globular clusters, on average, than other dwarf galaxies with similar luminosities. The UDG NGC 5846-UDG1 is among the most extreme examples of globular cluster-rich galaxies found so far. Here we present new Hubble Space Telescope observations and analysis of this galaxy and its globular cluster system. We find that NGC 5846-UDG1 hosts 54 ± 9 globular clusters, three to four times more than any previously known galaxy with a similar luminosity and higher than reported in previous studies. With a galaxy luminosity of L V,gal ≈ 6 × 107 L ⊙ (M ⋆ ≈ 1.2 × 108 M ⊙) and a total globular cluster luminosity of L V,GCs ≈ 7.6 × 106 L ⊙, we find that the clusters currently comprise ∼13% of the total light. Taking into account the effects of mass loss from clusters during their formation and throughout their lifetime, we infer that most of the stars in the galaxy likely formed in globular clusters, and very little to no “normal” low-density star formation occurred. This result implies that the most extreme conditions during early galaxy formation promoted star formation in massive and dense clumps, in contrast to the dispersed star formation observed in galaxies today.